Earth-abundant and environment friendly organic–inorganic hybrid tetrachloroferrate salt CH3NH3FeCl4: structure, adsorption properties and photoelectric behavior. Issue 36 (30th May 2018) - Yin, Jie; Shi, Shaozhen; Wei, Jiazhen; He, Guohang; Fan, Lin; Guo, Junxue; Zhang, Kaixuan; Xu, Wenli; Yuan, Cang; Wang, Yunying; Wang, Liwen; Pu, Xipeng; et al.
Abstract : We prepare earth-abundant and environmentally friendly organic–inorganic hybrid tetrachloroferrate salt CH3 NH3 FeCl4 (MAFeCl4 ) for optoelectronic applications. Abstract : Organic–inorganic hybrid-based lead perovskites show inherent and unavoidable problems such as structural instability and toxicity. Therefore, developing low-cost and environment-friendly organic–inorganic hybrid materials is extremely urgent. In this study, we prepared earth-abundant and environment-friendly organic–inorganic hybrid tetrachloroferrate salt CH3 NH3 FeCl4 (MAFeCl4 ) for optoelectronic applications. The single crystal diffraction data are assigned to the orthorhombic MAFeCl4 ( Pnma space group), with parameters a = 11.453 (5) Å, b = 7.332 (3) Å, c = 10.107 (5) Å, α = 90.000, β = 90.000, and γ = 90.000. The band gap of MAFeCl4 is approximately 2.15 eV. Moreover, three-emission luminescence (398, 432 and 664 nm) was observed. To the best of our knowledge, this is the first study involving the investigation of the structure, adsorption properties and photoelectric behavior of MAFeCl4 . A low cost photodetector based on the MAFeCl4 thin film is efficient under different monochromatic light from 330 nm to 410 nm with different chopping frequencies (1.33 Hz to 40 Hz). The photoelectric conversion efficiency based on FTO/TiO2 /MAFeCl4 /carbon electrode device reaches 0.054% ( V oc = 319 mV, J sc = 0.375 mA cm −2, and fill factor = 0.45) under AM1.5, 100 mW cm −2 simulated illumination. Our findings will attract attention from the magnetic, piezoelectric and photoelectronic research fields.